PENGARUH FASILITAS KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI KANTOR DESA MALANG NENGAH KECAMATAN PAGEDANGAN, BANTEN - Lisa Umami; Haidilia Maharani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
employee performance at the Malang Nengah Village Office, Pagedangan District, Banten. Adequate work facilities and an effective leadership style are believed to be important factors in improving employee productivity and performance. This study used quantitative methods with an associative and descriptive approach. The study population was all 53 village office employees, with a random sampling technique based on the Slovin formula.Data were collected through questionnaires and analyzed using multiple linear regression and t- and F-tests. The results showed that work facilities had a positive and significant effect on employee performance with a t-value of 2.152 (Sig. 0.036 < 0.05), and leadership style also had a positive and significant effect on employee performance with a t-value of 2.649 (Sig. 0.011 < 0.05). Simultaneously, work facilities and leadership style significantly influenced employee performance with an F-value of 39.159 (Sig. 0.000 < 0.05). Multiple linear regression produces the equation: Y = 13.320 + 0.337X1 + 0.346X2, which shows that improving work facilities and leadership style will improve employee performance.